2019
DOI: 10.15377/2409-9821.2019.06.5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Control Strategies for the Radiant Floor Cooling System Combined with Displacement Ventilation: A Case study of an Office Building in Jinan, China

Abstract: The radiant floor cooling system, as a thermally activated building system, has attracted significant attention as it can save energy consumption and shift the building load. However, due to its characteristic that building thermal mass has a significant influence on the system performance and indoor environment, the control strategies should be seriously accounted for. Moreover, its performance is highly related to the shift condition of cooling load during the daytime and different weather conditions, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Thermal performance of the radiant terminal can be effectively used by applying an intermittent control strategy combined with controlling supply water temperature and flow rate in radiant panels, this contributes to improve response time. Liu et al [11] showed that the energy consumption decreased by 3.3% to 7.5% when the different intermittent operation strategies using thermal characteristic of the building were applied. Hu et al [12] found that radiant cooling system conserved cooling energy in unoccupied period to balance 9-15% of indoor heat gain in occupied period, and the peak sensible cooling loads of the radiant terminal decreased by 32-39% compared with those using conventional scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal performance of the radiant terminal can be effectively used by applying an intermittent control strategy combined with controlling supply water temperature and flow rate in radiant panels, this contributes to improve response time. Liu et al [11] showed that the energy consumption decreased by 3.3% to 7.5% when the different intermittent operation strategies using thermal characteristic of the building were applied. Hu et al [12] found that radiant cooling system conserved cooling energy in unoccupied period to balance 9-15% of indoor heat gain in occupied period, and the peak sensible cooling loads of the radiant terminal decreased by 32-39% compared with those using conventional scheduling.…”
Section: Introductionmentioning
confidence: 99%